Biochanin A Alleviates Cerebral Ischemia/Reperfusion Injury by Suppressing Endoplasmic Reticulum Stress-Induced Apoptosis and p38MAPK Signaling Pathway In Vivo and In Vitro - Guo, Min-min; Qu, Sheng-biao; Lu, Hui-ling; Wang, Wen-bo; He, Mu-Liang; Su, Jian-Lin; Chen, Jian; Wang, Yong (Frontiers in Endocrinology, 2021)
We have previously shown that biochanin A exhibits neuroprotective properties in the context of cerebral ischemia/reperfusion (I/R) injury. The mechanistic basis for such properties, however, remains poorly understood. This study was therefore designed to explore the manner whereby biochanin A controls endoplasmic reticulum (ER) stress, apoptosis, and inflammation within fetal rat primary cortical neurons in response to oxygen-glucose deprivation/ reoxygenation (OGD/R) injury, and in a rat model of middle cerebral artery occlusion and reperfusion (MCAO/R) injury. For the OGD/R in vitro model system, cells were evaluated after a 2 h OGD following a 24 h reoxygenation period, whereas in vivo neurological deficits were evaluated following 2 h of ischemia and 24 h of reperfusion. The expression of proteins associated with apoptosis, ER stress (ERS), and p38 MAPK phosphorylation was evaluated in these samples. Rats treated with biochanin A exhibited reduced neurological deficits relative to control rats following MCAO/R injury. Additionally, GRP78 and CHOP levels rose following I/R modeling both in vitro and in vivo, whereas biochanin A treatment was associated with reductions in CHOP levels but further increases in GRP78 levels. In addition, OGD/R or MCAO/R were associated with markedly enhanced p38 MAPK phosphorylation that was alleviated by biochanin A treatment. Similarly, OGD/R or MCAO/R injury resulted in increases in caspase-3, caspase-12, and Bax levels as well as decreases in Bcl-2 levels, whereas biochanin A treatment was sufficient to reverse these phenotypes. Together, these findings thus demonstrate that biochanin A can alleviate cerebral I/R-induced damage at least in part via suppressing apoptosis, ER stress, and p38 MAPK signaling, thereby serving as a potent neuroprotective agent.